IMPROVING THE TAXATION PROCEDURE FOR FOREIGN TRADE ACTIVITIES: PROBLEMS, CUSTOMS CONTROL AND INSTITUTIONAL SOLUTIONS (American Journal of Business Management, Economics and Banking, 2026)
The article examines practical directions for improving the taxation procedure for foreign trade activities based on an analysis of the problems of the tax burden, bad and overdue debts arising from foreign trade operations, double taxation, as well as the mechanisms of customs control and digital administration. It is substantiated that the effectiveness of tax and customs regulation depends not only on rates and benefits, but also on the quality of contract monitoring, the transparency of customs valuation, the use of electronic declarations, risk-oriented control and post-clearance audit. Special attention is paid to the stimulating and compensatory mechanism of asset repatriation, the recognition of certain types of debt as bad debts, the simplification of VAT offset for exported goods and the expansion of digital data exchange among tax, customs and banking institutions. The conclusion is made that it is necessary to move from fragmented control to an integrated model of foreign trade administration that combines fiscal effectiveness, support for bona fide business and a reduction in administrative costs.